Find the general solution to the following second

afasiask7xg 2022-03-23 Answered
Find the general solution to the following second order differential equations.
y5y=0
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (2)

Jambrichp2w2
Answered 2022-03-24 Author has 12 answers

First finding the solutions to the given second-order differential equation by forming the auxiliary equation
Let us take dydx=D
Then we have,
D25=0
D2=5
D=±5
We know when the solutions to the auxiliary equation are identical and of opposite sign then the general solution to the given differential equation is
y=c1eat+c2ebt
Here,
a=5, b=5
Therefore the general solution to the given differential equation is
y=c1e5t+c2e-5t

Not exactly what you’re looking for?
Ask My Question
Jeffrey Jordon
Answered 2022-03-31 Author has 2262 answers

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2021-12-31
Find the solution of the following Differential Equations
(2x+ey)dx+xeydy=0
asked 2022-05-31
I am looking to solve the following equations numerically:
a x = d d t ( f ( x , y , t ) d y d t ) , b y = d d t ( g ( x , y , t ) d x d t )
For arbitrary functions f and g and constants a and b. I am struggling to find a way to transform this into a system of first order differential equations that I can pass into a solver. It looks like I will need to define these implicitly, but I'm not sure how to do that.
My best attempt so far is the following:
z 1 = f ( x , y , t ) d y d t z 2 = g ( x , y , t ) d x d t z 3 = a x z 4 = b y
( z 1 z 2 z 3 z 4 ) = ( 0 0 1 0 0 0 0 1 0 a g ( t , x , y ) 0 0 b f ( t , x , y ) 0 0 0 ) ( z 1 z 2 z 3 z 4 )
However, this seems fairly inelegant and assumes that you are always able to divide by f and g. I'm trying to keep this as general as possible, so don't want to make that assumption. Is there a better way to turn this into a system of first order differential equations implicitly?
asked 2021-02-12

Use the definition of Laplace Transforms to show that:
L{tn}=n!sn+1,n=1,2,3,

asked 2022-01-20
Does ODE initial value problem produce beat or resonance phenomenon?
x+9x=sin(3t)
x(0)=x(0)=0.
We are allowed to solve differential equations with TI-89.
asked 2022-01-17
Find the general solution to the differential equation
dydt=t3+2t28t
Also, part 8B. asks: Show that the constant function y(t)=0 is a solution.
Ive
asked 2021-09-07

Use Laplace transform to solve the initial-value problem
y=3,y(0)=1,y(0)=1

asked 2022-05-09
Use linear approximation, i.e. the tangent line, to approximate 11.2 2 as follows :
Let f ( x ) = x 2 and find the equation of the tangent line to f ( x ) at x = 11. Using this, find your approximation for 11.2 2 .